Estimating the Effect of Corporate Social Responsibility on Firm Value Using Geographic Identification. (29th April 2017) - Chintrakarn, Pandej; Jiraporn, Pornsit; Jiraporn, Napatsorn; Davidson, Travis
Abstract: We argue that firms located close to one another tend to have similar corporate social responsibility (CSR) policies, due to investor clienteles, local competition, as well as social interactions. Our results are consistent with this notion. In particular, firms located in the same 3‐digit zip code exhibit a similar degree of CSR. Exploiting the variation in CSR across zip codes, we estimate the effect of CSR on firm value. Part of the firm's CSR is induced by the surrounding firms in the same zip code and can be considered exogenous as it is determined outside the firm. Because zip code allocation is based on efficiency in mail delivery, and not on corporate policies or outcomes, it is likely exogenous. Our instrumental variable analysis reveals that more socially responsible firms enjoy significantly higher firm value. We confirm the results using phone number area codes, instead of zip codes, and reach the same conclusion.